Microalgal biotechnology : potential and production - Posten, Clemens; Walter, Christian, 1965 December 15- (Walter de Gruyter, 2012)
With the high interest in renewable resources, the field of algal biotechnology has undergone a huge leap in importance. This book treats the biological fundamentals of microalgal biotechnology in physiology and molecular biology. It provides an overview of applications and products as well as a survey of the state-of-the-art in process engineering of algae cultivation. So this book will be of interest to active people in the area of sustainable production of high value products or mass production of food and fuel for the future.